Pengaruh Fasilitas, Pelayanan, dan Kebutuhan terhadap Minat Baca Mahasiswa Politeknik Negeri Medan - Novi Ardana; Dewi Comala Sari; Safaruddin Safaruddin; Ika Mary Pasaribu (Jurnal Riset Rumpun Ilmu Ekonomi, 2025)
The research is entitled The Influence of Facilities, Services and Needs on the Reading Interest of Medan State Polytechnic Students, with the research objective being to determine the Influence of Facilities, Services and Needs on the Reading Interest of Medan State Polytechnic Students with this research method, namely Quantitative with data collection methods Observation, Study Libraries, and Questionnaires. Meanwhile, this research was tested using SPSS version 25 statistics which found the results of a positive influence between the independent variable on the dependent variable. Based on the research results it was found that Facilities had an influence tcount of 2.636 > 1.988, while on the results of the Service variable the tcount was 2.243 > 1.988, However, the Requirements variable found a t-count result of 3.567 > 1.988. This result can also be seen as an overall influence in the Coefficient of Determination test which shows a result of 0.355 or 35.5%, where the remaining 64.5% of the figure is influenced by other variables. Based on the research results, it was agreed that the facilities, services and needs to increase students' reading interest as visitors must be improved further.